Posttraumatic Growth And Psychosocial, Cancer And Treatment Related Factors In Head And Neck Cancer: Assessing Their Associations In A Cross-Sectional Study - Hamdan, Nur Amirah (2022)
This cross-sectional study aimed to translate and validate the Fear of Progression Questionnaire-Short Form (FoP-Q-SF) and Cancer Treatment Satisfaction Questionnaire (CTSQ) into Malay (phase 1 of the study) and to determine the associations between unmet supportive needs, fear of cancer progression, healthrelated quality of life, expectation and satisfaction with cancer therapy, and posttraumatic growth (PTG) among a group of head and neck cancer (HNC) patients (phase 2 of the study).